Efek konsumsi yogurt terhadap glukosa darah puasa pada penyandang diabetes melitus tipe 2 - Nuriannisa, Farah; Kertia, Nyoman; Lestari, Lily Arsanti (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2019)
Background: Generally, patients with type 2 diabetes mellitus (T2D) have dysbiosis condition. Dysbiosis can increase oxidative stress that leads to hyperglycemia. Previous researches showed that yogurt consumption can reduce blood glucose in T2D, so it can be used as an alternative healthy snack for T2D patients.Objectives: To investigate the effects of probiotic and conventional yogurt with dosage 100ml/day on fasting blood glucose (FBG) in T2D patientsMethods: Randomized controlled trial, double blind with pre-post group design. The 30 T2D patients from 3 publics health centre in Yogyakarta, were assigned to two groups. Each group, either control or intervention group, received 100 ml/d of yogurt for 4 weeks. FBG samples was assessed before and after intervention periodResults: FBG significantly decreased in both group, which was -27 mg/dL in control group (p<0.05) and -19 mg/dL in intervention group (p<0.05). No significant difference in FBG change between intervention and control group, but control group has greater reduction in FBG compared to intervention group. Conclusion: Conventional yogurt has no significant difference effect in FBG change compared to probiotic yogurt.Â